ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA DALAM PENGAMBILAN KEPUTUSAN MEMILIH PROGRAM STUDI AKUNTANSI UNIVERSITAS PANCA BHAKTI DI KOTA PONTIANAK - Nadia, Christine; Risal; Wulandari Chairina, Septi; Mayasafitri, Rina (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
This research aims to determine the influence of: (1) Study program image on students' interest in choosing the Panca Bhakti University Accounting Study Program, (2) Education costs on students' interest in choosing the Panca Bhakti University Accounting Study Program, (3) Environmental factors on students' interest in choosing the Study Program Panca Bhakti University Accounting, (4) Level of Difficulty regarding student interest in choosing the Panca Bhakti University Accounting Study Program. The research respondents were high school and vocational school students in class XII in Pontianak with a total of 99 respondents. Analysis testing includes validity test, reliability test, normality test, heteroscadesity test, multicollinearity test. The data analysis technique used is multiple linear regression analysis. The research results show that the study program image variable (X1) has a significant level (0.310>0.05), so the study program image variable has no effect on student interest. Then for the Education Cost variable (X2) with a significant level (0.724>0.05), the Education Cost variable has no effect on Student Interest. Then for the Environmental Factor variable (X3) with a significant level (0.000<0.05), the Environmental Factor variable has a significant effect on Student Interest. And for the Difficulty Level variable (X4) with a significant level (0.403<0.05), the Difficulty Level variable has no effect on Student Interest. Based on the results of the F test with a significance level of 5%, the sig value is 0.000 < 0.05, it can be concluded that the variables X1 study program image, majoring in accounting at Panca Bhakti University Pontianak (Y).